2013
DOI: 10.1002/cbf.2957
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester modulates aflatoxin B1‐induced hepatotoxicity in rats

Abstract: Aflatoxin B1 (AFB1) is the most potent of the mycotoxins and is widely observed in nutrition abnormalities. There are some studies suggesting oxidative stress-induced toxic changes on liver related to AFB1 toxicity. The aim of the present study was to evaluate whether antioxidant caffeic acid phenethyl ester (CAPE) relieves oxidative stress in AFB1-induced liver injury in rat. Twenty-four male rats were equally divided into three groups. The first group was used as a control. The second group received three do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…For example, CAPE, injected intraperitoneally ( i.p .) to 10–12 weeks old male Wistar albino rats (10 mg/kg body mass; 10-days administration), revealed protective effects on the aflatoxin B1-induced hepatoxicity by modulating free radical production: it decreased the total oxidant capacity (TOC) and glutathione S-transferase activity [23]. In another study, CAPE, given i.p .…”
Section: Discussionmentioning
confidence: 99%
“…For example, CAPE, injected intraperitoneally ( i.p .) to 10–12 weeks old male Wistar albino rats (10 mg/kg body mass; 10-days administration), revealed protective effects on the aflatoxin B1-induced hepatoxicity by modulating free radical production: it decreased the total oxidant capacity (TOC) and glutathione S-transferase activity [23]. In another study, CAPE, given i.p .…”
Section: Discussionmentioning
confidence: 99%
“…Rats under a carcinogenic protocol ( N ‐diethylnitrosamine) showed decreased number of preneoplastic nodules and reduced incidence of liver tumors when pretreated with CAPE. Akcam et al recently indicated that CAPE could protect against aflatoxin B1‐induced hepatotoxicity via modulating free radical production. This was evidenced through normalized biochemical values and histopathology.…”
Section: Biological Activities Of Capementioning
confidence: 97%
“…Number of animals used in this study was based on earlier aflatoxin studies. 8 Determination of oral aflatoxin 31,32 and Tarantula cubensis D6 dose, 13 previous studies were based on but some modifications were made on application period for Tarantula cubensis D6 considering the severity of aflatoxin intoxication. The protocol of the present study was approved by the Ethics Board for Experimental Animals of Erciyes University.…”
Section: Animal Materialsmentioning
confidence: 99%